Disturbance observer–based control of flexible hypersonic flight vehicle. (27th March 2017) - Ren, Jianxin; Yang, Daipeng
In this article, the disturbance observer–based control is designed for a flexible hypersonic flight vehicle with the external disturbance. The aircraft structure is easy to cause elastic vibration, thus leading to serious change in structural configuration or even disintegration. Therefore, the impact of elasticity modal for altitude subsystem is described as a system disturbance, and then, the equivalent model is established. On this basis, considering the model structure and composition of nonlinear systems, the disturbance observer is used to eliminate the information of the disturbance. Finally, the simulation results make an offer to show that the disturbance observer–based control can provide a good tracking performance.